Peningkatan Kualitas UMKM di Kelurahan Tlogopatut, Kecamatan Gresik, Kabupaten Gresik melalui Pemanfaatan Media Sosial dan E-Commerce - Zulyanto, Agus; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
This journal discusses a community service program which aims to improve the quality of micro,small and medium enterprise in Tlogopatut Village, Gresik District, Gresik Regency through the useof digital technology. This program aims to significantly improve the MSME sector in the region,recognizing the important role of MSME in the local economy and working to reduce the digitaldivide in access to technology in society. This program includes several steps, including identifyingdigital technology needs for local MSME, providing training in using relevant software andapplications, and supporting the use of e-commerce platforms to promote and sell MSME productsonline. The results of this program show a significant increase in MSME access to digital technologyas well as income growth and expanding the scope of their consumers. In addition, this program alsohelps increase consumer awareness of local MSME products through e-commerce platforms, thussupporting economic growth in the Tlogopatut sub-district area. This community service hassucceeded in connecting MSME with digital technology so that they are able to compete in anincreasingly connected and online-based economy. These results reflect important efforts to improvethe quality of MSME in the region and provide valuable learning about the importance of digitaltechnology in supporting local economic growth and exchange.Keywords: Community Service; Training; MSME; E - Commerce